Islamic Corporate Governance: Pengaruh Tingkat Pedidikan dan Keahlian Keuangan Dewan Pengawas Syariah (DPS) terhadap Perilaku Pengambilan Risiko - Luciana Luthan (Wahana Riset Akuntansi, 2021)
This study examines the effect of DPS characteristics on risk-taking behavior in Indonesian Islamic banking in 2010-2016. The first characteristic tested is the level of education and the second is SSB expertise in finance. The population of this research is Islamic banks in Indonesia, while the sample consists of 63 Islamic commercial banks in Indonesia, which were selected by purposive sampling method. The measurement used for the education level of DPS is the percentage of DPS with a master's degree, while for financial expertise it is used the percentage of DPS who have expertise in finance. Then to measure the bank's risk-taking behavior, the Z-score is used. The results of hypothesis testing indicate that hypotheses 1 and 2 are accepted. From the results of the study, it can be concluded that the higher the education level of DPS, will encourage Islamic banks to take bigger risks. And the increasing number of SSB members who have a background of expertise in finance will limit Islamic banks in taking risks.Keywords: Islamic Corporate Governance; Sharia Supervisory Board (SSB); Islamic Bank; Risk Taking Behaviour.